New composite timbers: full-field analysis of adhesive behavior. (April 2014) - Clouet, Boris; Pommier, Régis; Danis, Michel
Green gluing technology may have a large interest in wood industry. It allows energy saving, thus reducing costs. In order to fulfill requirements in relevant building codes and standards, these composite timbers have to present sufficient structural performance and shape stability. The drying step during the process of green gluing may lead to local strain and stress developments on the adhesive interface. These strain and stress developments could impact the shape stability of the product and induce joint failure. However, wood spatial microstructure may absorb these developments. It has to be noted that for an organic material such as wood, the measurement of hygromechanical properties must be done without any interactions between the material and the measurement system. In order to process in this way, an optical measurement system such as the digital image correlation has been used. Results have shown the local behavior of the interface during shrinkage of wood. The strains of the adhesive bond were calculated from the measurement by means of an inverse method.